2014
DOI: 10.1007/s10695-014-9944-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional effects of early exposure to 4-nonylphenol on gonadal development of Nile tilapia (Oreochromis niloticus): b-histological alterations in testes

Abstract: The present study investigates the effects of different doses (0, 40, 60, 100 μg/L) of 4-nonylphenol (NP) on testis histology and sperms motility of mature Oreochromis niloticus. A tendency for a dose-dependent reduction in the gonado-somatic index (GSI) in the NP-exposed groups was observed. Histological examination revealed that high doses of NP (60 and 100 μg/L) cause hyperplasia of interlobular connective tissue components coincide with decrease in the size of seminiferous lobules and amount of lumen sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Triclosan exposure significantly affected the gonadosomatic index in both sexes consistent with a previous study after sublethal exposure of chlordecone for 30 days to the cichlid fish, Pseudetroplus maculatus (Asifa and Chitra, 2019). Nile tilapia Oreochromis niloticus exposed to nonylphenol, an estrogenic compound, has been shown to cause a decline in GSI, which was found associated with histological lesions in the ovary, and reduction in the levels of estradiol and vitellogenin in the female fish (El-Sayed Ali et al, 2014). Similarly, male Nile tilapia exposed to diuron and its metabolites saw a reduction in GSI and altered testicular histology with a profound reduction in the levels of testosterone and 11-ketotestosterone thereby suggesting anti-androgenic activity of the herbicide (Pereira et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Triclosan exposure significantly affected the gonadosomatic index in both sexes consistent with a previous study after sublethal exposure of chlordecone for 30 days to the cichlid fish, Pseudetroplus maculatus (Asifa and Chitra, 2019). Nile tilapia Oreochromis niloticus exposed to nonylphenol, an estrogenic compound, has been shown to cause a decline in GSI, which was found associated with histological lesions in the ovary, and reduction in the levels of estradiol and vitellogenin in the female fish (El-Sayed Ali et al, 2014). Similarly, male Nile tilapia exposed to diuron and its metabolites saw a reduction in GSI and altered testicular histology with a profound reduction in the levels of testosterone and 11-ketotestosterone thereby suggesting anti-androgenic activity of the herbicide (Pereira et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that 4-NP sequesters in the liver, brain, gills, gonads, and tissues of fish (Ahel et al, 1994;Lewis and Lech, 1996;Coldham et al, 1998) and can cause negative consequences for reproduction and development (Colborn et al, 1993;Jobling et al, 1996;Christiansen et al, 1998;Tabata et al, 2001;Chandrasekar et al, 2011). Male fish exposed to 4-NP, for instance, have been found to exhibit a suite of defects including altered testicular structure, decreased sperm counts, intersex gonads, disrupted reproductive cycles, liver damage, and reduced growth (e.g., Christiansen et al, 1998;Servos, 1999;Tanaka and Grizzle, 2002;Kaptaner and € Unal, 2011;El-Sayed Ali et al, 2014;Traversi et al, 2014). And, even though 4-NP is approximately 1500 times less potent than E2 (Butwell et al, 2002), exposure to 4-NP either at concentrations in the range found commonly in sewage effluents or for only a brief duration of exposure is capable of activating intracellular ERs and inducing the expression of estrogen-regulated genes in juvenile and male fish (e.g., Soto et al, 1991;White et al, 1994;Arukwe et al, 2001Arukwe et al, , 2002Ackermann et al, 2002;Genovese et al, 2011;Brander et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, concern has been increased regarding chemicals in the environment with the capacity to alter normal endocrine function in wildlife. The sources of such chemicals are diverse and effects have been observed in many vertebrates (El-Sayed Ali et al, 2014) Polybrominated diphenyl ethers (PBDEs) are considered a class of such chemicals and are called organohalogens. These organohalogen compounds are produced in large quantities and are used extensively as flame-retardants in a wide range of products being ubiquitous in the environment (van Boxtel et al, 2008).…”
Section: Introductionmentioning
confidence: 99%